Investigating small mammal community structure as a possible indicator of improved habitat integrity in an area cleared of alien vegetation - De Klerk, Jean J. (University of the Free State, 2014)
Small mammal communities have been identified as possible indicators of the ecological integrity of different areas. Small mammal species are adapted to micro habitats and therefore can be affected by small-scale changes, which can be monitored to assist in biodiversity studies. Alien vegetation eradication programs have been ongoing across many areas of South Africa. These eradicated areas are believed to be able to restore to the original condition and therefore improving the biodiversity of the area. However, many ways of assessing ecological integrity are time consuming and expensive. By assessing the small mammal diversity and community structure in eradicated areas, judgments could be made about the success of implemented eradication programs. As small mammal surveys can be done readily, the ability to use them as indicators allows them to be implemented in all eradicated areas to indicate conditions of area over various time periods and can be utilized on a continual basis. This study investigates to which extent small mammal community structure (including the specific species present and the species richness) could indicate improved habitat integrity in areas cleared of alien vegetation. Small mammal communities in three areas, (i) area infested with Black Wattle (Acacia mearnsii), (ii) area cleared of Black Wattle and (iii) a control area which have no records of alien vegetation, were assessed. Data was captured using PVC live traps similar to Sherman and Willan traps. Traps were placed along transects in each area, once a month, from October to December 2013 for four consecutive days at a time. A total of 690 individual were caught during the 5400 trap nights of the study, with an overall trap success of 12.78%. In total five small mammal species were caught; one musk shrew (Crocidura flavescens) and four rodents. There was a significant difference between the number of small mammals caught between the three areas, with the control area and the cleared area being the most similar. Both the Shannon-Wiener and the Simpson’s diversity indexes were used, with the Shannon-Wiener indicating some significant differences between the areas and the Simpson’s indicating that there was not a significant difference between the areas. The Friedman Anova indicated a significant difference in the amount of species caught between the areas, with the Wilcoxon test indicating that there was significantly less species in the infested than in both the control and cleared areas; no difference was found between the cleared and the control areas. A similar difference in the total amount of individuals caught was also found. This was also found for the three most numerous species Rhabdomys pumilio, Micaelamys namaquensis, Otomys irroratus. Two species Saccostomus campestris and Crocidura flavescens were found in low numbers at both the control and cleared plots, but could not be found at the infested site. This study indicates that small mammal communities are different between the areas sampled with the infested area having the lowest species richness and abundance. The cleared area is not significantly different from the control area, but has a significantly higher species richness and abundance than the infested area, indicating that the area has improved and that small mammals could be used as an indicator of ecological integrity after alien eradication. No clear indicator species were identified, due to only five species being recorded. Rhabdomys pumilio dominated all areas sampled and has been identified to occur from very disturbed to pristine areas. Where more time and assistance is available, future studies will benefit from the inclusion of ecological integrity indices on other taxa, such as vegetation, alongside the small mammal communities. This would allow for correlations to be drawn and report on integrity at different levels of the ecosystem. As such the ecological integrity of the area can be determined using already proven indices to compare with the small mammal results. A further recommendation is that future small mammal studies should also include extended seasonal sampling including autumn and winter which have proved to yield higher trap success.
Dissertation (M.E.M. (Centre for Environmental Management))--University of the Free State, 2014
Keywords: Mammals -- Effect of habitat modificaton; Alien plants